Desain Media Informasi Obat pada Platform Tiktok Terhadap Fenome Stunting di Kota Jambi - Raihana Salsabila; Rizky Yulion Putra; Deni Sutrisno (Journal of Innovative and Creativity, 2025)
Stunting is a chronic nutritional problem that has a serious impact on children's growth and development, and its prevalence is still high in Jambi City. The lack of public understanding of stunting, including information about the right medications, is one of the important factors that need to be addressed. This research aims to design an effective and attractive drug information media through the TikTok platform to increase public awareness and knowledge about stunting in Jambi City. This research uses the design and development method with a quantitative approach. The stages include needs analysis, drug information media content design, prototype development, implementation, and evaluation. Data was collected through pre-test and post-test on the same target group before and after being given information media intervention through the TikTok platform. Data analysis used a paired sample t-test to determine the significant differences between public knowledge before and after exposure to information media. The results of the study show that the TikTok platform has great potential as an effective information medium due to its popularity among the public, including young mothers who are the main targets in stunting prevention. The content of the drug information media is designed to include short educational videos, animations, infographics, and testimonials that are presented in an attractive and easy-to-understand manner. The results of the paired sample t-test showed a significant difference between public knowledge before and after being given information media intervention through the TikTok platform. This study concludes that the design of drug information media on the TikTok platform can be an effective strategy in overcoming the problem of stunting in Jambi City. Interesting and easily accessible information media through digital platforms can increase public awareness and knowledge about stunting, so it is expected to contribute to efforts to prevent and control stunting in the area